2014
DOI: 10.1039/c4ra03873h
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of plasma electrolytic oxidation on valve metals by means of molecular spectroscopy – a review

Abstract: A review of results of molecular spectroscopic investigations during plasma electrolytic oxidation of valve metals is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 142 publications
(132 reference statements)
0
32
0
Order By: Relevance
“…Ref. [20] and references therein). In contrast, the appearance of atomic and ionic lines originating from the metallic substrate depends on its melting point and/or on the electrolyte used for anodization [18,25,26].…”
Section: Luminescence During the Anodization Of Niobiummentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [20] and references therein). In contrast, the appearance of atomic and ionic lines originating from the metallic substrate depends on its melting point and/or on the electrolyte used for anodization [18,25,26].…”
Section: Luminescence During the Anodization Of Niobiummentioning
confidence: 99%
“…It has been shown that luminescence spectrum during the spark discharging of metals is composed of continuum radiation and spectral lines [19,20]. Continuum radiation results from the radiative recombination of electrons at defects in oxide films and bremsstrahlung radiation [19].…”
Section: Luminescence During the Anodization Of Niobiummentioning
confidence: 99%
“…members of the band sequence v′ = v″. For a comprehensive review of experimental and theoretical studies on this system the reader is referred to our recent studies [7,21,25].…”
Section: Spectroscopic Characterization Of Peo Processmentioning
confidence: 99%
“…or metallic alloys [7]. This process involves anodizing above the dielectric breakdown voltage and leads to the formation of localized plasma microdischarges.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain such composites one can use plasma electrolytic oxidation (PEO) technique [1,[3][4][5] that is electrochemical oxidation of valve metals under spark and microarc electric discharges [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%